TECHNOLOGY ACCEPTANCE AND LEARNING MOTIVATION IN CALL AND MALL: A QUANTITATIVE STUDY EXTENDING TAM IN INDONESIAN VOCATIONAL HIGH SCHOOLS - Masfufah Zahiroh; Slamet Asari (English Review: Journal of English Education, 2026)
This quantitative study examined technology acceptance and learning motivation in Computer-Assisted Language Learning (CALL) and Mobile-Assisted Language Learning (MALL) environments by extending the Technology Acceptance Model (TAM) with motivational factors. The study addressed two research questions: (1) How do perceived usefulness, perceived ease of use, and learning motivation influence students' behavioral intention to use CALL and MALL? (2) To what extent does the extended TAM model explain variance in technology acceptance? Data were collected from 72 eleventh-grade vocational high school students at SMK PGRI 3 Tanggul, Indonesia, using a Likert-scale questionnaire. Descriptive statistics, Pearson correlation, and linear regression analyses were employed. Results indicated high mean scores across all variables (range: 4.05-4.26). Learning motivation demonstrated the strongest correlation with behavioral intention (r=0.789). The extended TAM model explained 70.9% of variance in behavioral intention (R²=0.709), with learning motivation as the strongest predictor (β=0.814), followed by perceived usefulness (β=0.341) and perceived ease of use (β=0.256). These findings suggest that integrating motivational factors into TAM provides a more comprehensive framework for understanding technology acceptance in CALL and MALL environments. Limitations include single-site sampling and reliance on self-reported data, which may limit generalizability. Implications for pedagogy and curriculum design in vocational EFL contexts are discussed.